POTENSI AGENSIA HAYATI DALAM MENEKAN LAJU SERANGAN PENYAKIT BLAS (Pyricularia oryzae) PADA TANAMAN PADI - Eka Kusumawati, Dian; Istiqomah, Istiqomah (Universitas Islam Balitar, 2020)
Blast disease is an important disease that affects many rice plants. Blasts can damage rice leaves (leaf blasts), nodes (node blasts), neck blasts, colar blasts and rice grains. Symptoms on the leaves are rhombic-shaped spots with a tapered tip. The center of the patch is gray surrounded by brown to reddish brown on the edge of the spot. The color of the spots at the beginning of the symptoms is white or gray, surrounded by green-brown. Based on market demand, agricultural products that are safe and healthy for consumers as well as environmentally friendly are increasing, therefore controlling plant pathogens by using antagonistic microorganisms is one of the ways that must be considered. A number of microbes have been widely tested and are quite effective in controlling plant pathogens. PGPR and Streptomyces are biological agents that are able to reduce the level of attack of plant diseases, especially in rice blast disease. This study used a comparative method between rice cultivation and biological agent applications and rice cultivation without biological agents or control plant applications. The results obtained indicate that the application of biological agents can reduce the percentage of disease severity, reduce the percentage of infected leaves, the biological agents are also able to extend the incubation period, increase plant height growth, number of tillers and also the number of grains per panicle.